A busca estética de Edmund Burke : uma distinção entre o sublime e o belo - Prado, Gustavo Andrade (2019)
This research aims to investigate the aesthetic concepts of the Irish philosopher Edmund Burke (1729 – 1797). His legacy to civilization, with regard to his studies on the subject, was written in the words that constitute the ‘treatise’, as the author refers to the text, A Philosophical Inquiry into the Origin of our Ideas of the Sublime and the Beautiful, whose first edition was published in 1757. As a result of having devoted much of its existence to political life, he was eternalized in the lines of time with the book Reflections on the Revolution in France, of 1790, which gave him the eternal reputation of "father of conservatism." On the other hand, Immanuel Kant (1724-1804) considered him as the most important empiricist philosopher in aesthetic matters. In fact, Burke's treatise is informed by empiricism, although the author makes use of various methods, such as Newtonian induction as well as allusions to Cartesianism and other influences, in his search for glimpse a theory on the sublime and the beautiful, even being aware of the difficulties, and he limits himself to reassembling those attributes to their origins. A group of thinkers and currents of thought base his arguments, including philosophy, literature, (Catholic) religion, and science. This broad range sometimes obstructs the essence of the matrix that he tries to sketch with his concepts. Thus, this study will be moved to inquire whether Burke was successful in constructing an aesthetic theory, or how close he came to that goal. We will try to show that the Irish thinker sought this theory in the characterization and distinction of the sublime and the beautiful. At the end, we will make considerations about the taste and possible reasons for its diversity.